PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA TENAGA PENDIDIK PADA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI MANADO - Rumerung, Jeaneta; Muhammad K. Bakary; Mikke R.Marentek (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Knowledge management of teaching staff as intellectual capital for organizations majoring in Business Administration has not been implemented well, knowledge sharing has not been implemented to complement the competencies of teaching staff according to needs in the learning process. The research objectives are 1. to find out the process of knowledge management in the Business Administration department, 2. to find out the influence of knowledge management on the performance of teaching staff, 3. to find out how knowledge management is implemented in improving the performance of teaching staff. The research method used in this research is descriptive and verification methods. The descriptive research method aims to create systematic, factual and accurate descriptions, images or paintings regarding the facts, characteristics and relationships between the phenomena being investigated. The analysis technique uses descriptive analysis and verification analysis, data processing uses the SPSS program. The research results show that knowledge management has a significant effect on the performance of teaching staff in the Business Administration department of the Manado State Polytechnic. Implementation of knowledge management can be pursued through increasing personal knowledge, implementing job procedures (SOP) in the academic field, and applying technology to share knowledge so that it has a positive impact on improving performance. Keyword : Human Resource Management, Knowledge Management, Performance